ANALYSIS FACTORS - FACTORS AFFECTING DOMINANT BUDGET ABSORPTION (STUDY AT THE DEPARTMENT OF REVENUE, FINANCE AND ASSET MANAGEMENT KARAWANG DISTRICT) - Liya Megawati (Value : Journal of Management and Business, 2017)
The purpose of this study was to determine the effect of variable cash planning, budget execution, procurement, and monitoring and evaluation of budget absorption in the Department of Revenue, Finance and Asset Management Karawang District.The methodology used in this study using a quantitative approach to answer the type of explanatory hypotheses, with data analysis techniques using multiple linear regression statistical tests.The results obtained in which there is significant influence between the variables of variable absorption cash planning with a budget of 1.275, then the variable implementation of the budget with  variable absorption significant influence amounted to 0,147, then the variable procurement of goods and services with variable absorption significant influence amounted to 0,160, as well as monitoring and evaluation variables with variable absorption significant influence amounted to 0,527. The effect of variable cash planning, budget execution, procurement, and monitoring and evaluation of significant absorption with a coefficient of determination of 70.3%. this means that the three independent variables together have an influence on the dependent variable and 29.7% influenced by other variables.